Eksistensi Pemenuhan Pelayanan Kesehatan dan Makanan bagi Warga Binaan Lembaga Permasyarakatan Kelas I Makassar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to (i) find out and review the implementation of Article 9 letter D of Law No. 22 of 2022 in health and food services for class 1 Makassar inmates (ii) to find out and analyze the obstacles faced in providing adequate health and food services for class 1 Makassar inmates. The type of research used is qualitative with descriptive analysis which aims to describe the form of existence of the provision of health and food services for class I Makassar inmates. The data collection techniques are by conducting observations, interviews, and documentation. The data validation technique uses triangulation, namely to assess the credibility of the data which is carried out by checking the data that has been obtained through several sources. From the results of the study, it was found that (i) the implementation of Article 9 letter D of Law Number 22 of 2022 concerning health services and proper food has not been implemented optimally because it has not been fulfilled optimally (ii) the main obstacles in health services include limited medical personnel, minimal availability of certain medicines, health facilities that are still inadequate, a long and bureaucratic referral process, and prison overcapacity. Basically, efforts have been made and the services have been made but have not run optimally due to obstacles from the incomplete provision of medicines for health services, as well as a budget that is not balanced with the number of inmates in the Makassar Class 1 prison.